2016
DOI: 10.1136/medethics-2016-103370
|View full text |Cite
|
Sign up to set email alerts
|

Reasons doctors provide futile treatment at the end of life: a qualitative study

Abstract: Doctors believe that a range of factors contribute to the provision of futile treatment. A combination of strategies is necessary to reduce futile treatment, including better training for doctors who treat patients at the end of life, educating the community about the limits of medicine and the need to plan for death and dying, and structural reform at the hospital level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 44 publications
4
81
0
5
Order By: Relevance
“…Participants described defaulting to commence or continue resuscitation in situations of uncertainty or inexperience. Other studies have associated prognostic uncertainty with the provision of medically futile treatment and noted that confidence in determining futility21 and withholding or terminating curative treatment22 appeared to increase with experience. Research exploring reasons for non-compliance with termination of resuscitation protocols noted that lack of family emotional preparedness23 or family distress were commonly cited discretionary rationales 8…”
Section: Discussionmentioning
confidence: 99%
“…Participants described defaulting to commence or continue resuscitation in situations of uncertainty or inexperience. Other studies have associated prognostic uncertainty with the provision of medically futile treatment and noted that confidence in determining futility21 and withholding or terminating curative treatment22 appeared to increase with experience. Research exploring reasons for non-compliance with termination of resuscitation protocols noted that lack of family emotional preparedness23 or family distress were commonly cited discretionary rationales 8…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Willmott et al have reported why doctors provide futile treatments at the end of life 24. The drivers are multiple and powerful.…”
Section: Avoiding Nbts: Obstacles In the Waymentioning
confidence: 99%
“…Advances in medicine allow life to be prolonged, frequently in poor health, raising concerns over whether scarce health resources are being used wisely 1 2. Yet, as illustrated by the recent case of Charlie Gard,3 at the individual level, a decision to withhold or withdraw life-sustaining treatment can be difficult, and patients (or their substitute decision makers) may want treatment doctors believe is inappropriate 4. There are two distinct, but related, ethical rationales that a doctor could rely on to refuse such treatment 3 5–7.…”
Section: Introductionmentioning
confidence: 99%
“…This paper addresses this gap. Drawing on a larger project looking at how doctors conceptualise futile treatment,20 and the reasons they provide it,4 it reports on how doctors view the relationship between futility and resources, both conceptually and in their descriptions of their practice.…”
Section: Introductionmentioning
confidence: 99%